PATIENT SATISFACTION WITH FOOD SERVICE BY HOSPITAL NUTRITION UNIT: A STUDY IN A PRIVATE HOSPITAL - Kristianingsih, Rey; Wardani, Diadjeng Setya; Setiawati, Lisa (Universitas Brawijaya, 2025)
Food service by the nutrition unit to patients in hospitals is a complex service and requires special attention. Nutrition and diet that enter the patient's body are one of the supports for the recovery of the patient's health. However, plate waste, which is an indicator of patient satisfaction in food service by the nutrition unit, in case hospitals shows a fairly high figure. This study aims to find out the factors that cause food complaints from patients in the nutrition unit and observe what resources have been possessed by Panti Waluya Hospital in its potential to develop services. This research uses qualitative methods. The study was conducted using the Focus Group Discussion (FGD) method in each unit in the hospital and in-depth interviews with five inpatients to explore their satisfaction and expectations of food service in the hospital. The results of the interviews were then transcribed, and then thematic analysis was carried out. The results of the study showed that there were factors that caused patients to feel hesitant or dissatisfied with food service by the nutrition unit in the hospital, which included the factors of man, money, machine, and method. Through better education, it is hoped that it can increase patient satisfaction with food service by the nutrition unit by knowing the causative factors that cause patient dissatisfaction.